The origins of the institutions of marriage - Marina E. Adshade; Brooks A. Kaiser (Queen's University, Department of Economics, 2008)
Standard economic theories of household formation predict the rise of institutionalized polygyny in response to increased resource inequality among men. We propose a theory, within the framework of a matching model of marriage, in which, in some cases, institutionalized monogamy prevails, even when resources are unequally distributed, as a result of agricultural externalities that increase the presence of pair-bonding hormones. Within marriage, hormone levels contribute to the formation of the marital pair bond, the strength of which determines a man's willingness to invest in his wife's children. These pair bonds are reinforced through physical contact between the man and his wife and can be amplified by externalities produced by certain production technologies. Both the presence of additional wives and the absence of these externalities reduce the strength of the marital bond and, where the fitness of a child is increasing in paternal investment, reduce a woman's expected lifetime fertility. Multiple equilibria in terms of the dominant form of marriage (for example, polygyny or monogamy) are possible, if the surplus to a match is a function of reproductive success as well as material income. Using evidence from the Standard Cross Cultural Sample and Murdock's Ethnographic Atlas, we find that agricultural production externalities that affect neurological pair-bonding incentives significantly reduce the tendency to polygyny, even when resource inequality is present.
Keywords: J12; N30; O43; 330; Oxytocin; Vasopressin; Neurohormones; Marriage; Monogamy; Polygamy; Development of Institutions; Family structure; Ehe; Dauer; Vermögensverteilung; Biologie; Theorie